Concise commentary on income tax (Set of 2 Vol.) with tax planning/problems & solutions for A.Y. 2024-25 & 2025-2026 as amended the finance (no.2) act, 2024) - Ahuja, Girish; Gupta, Ravi (New Delhi Commercial Law, 2024)
Concise Commentary on Income Tax (Set of 2 Vol.) As Amended by Financial (No. 2) Act, 2024 EDITION 2025
Keywords: Law; Commercial Tax-Income Tax